TWO-DIMENSIONAL WATER SURFACE PROFILE ANALYSIS AT THE BEND OF PALU RIVER SEGMENT SP 304–SP 318 USING SMS AQUAVEO (RMA2 MODULE) - Nur Hidayat Nur; Nina Bariroh; Sitti Rahmi; I Gede Tunas; Vera W Andiese; Sri Warliawati (Postgraduate Tadulako University, 2026)
River bends are hydraulically complex zones characterised by centrifugal-force-driven secondary currents that produce differential water surface elevations, asymmetric velocity distributions, and lateral sediment transport. This study presents a two-dimensional (2D) hydrodynamic analysis of the water surface profile along a meandering reach of the Palu River (SP 304–SP 318), located in Tulo Village, Dolo District, Sigi Regency, Central Sulawesi, Indonesia. The RMA2 finite-element module within the Surface Modelling System (SMS) Aquaveo was employed. A 50-year return-period flood discharge (Q₅₀ = 387.85 m³/s) was estimated using the Snyder Synthetic Unit Hydrograph method, based on 15 years (2007–2021) of daily rainfall data from three meteorological stations. The Log Pearson Type III distribution was selected through Chi-square goodness-of-fit tests. A triangular 2D mesh at 5 m spacing was constructed in UTM Zone 49 WGS84 coordinates, and model calibration yielded a Manning roughness coefficient n = 0.01, matching the field-measured mid-channel velocity of 0.20 m/s. Under Q₅₀ conditions, the simulated maximum flow velocity is 2.88 m/s (SP 313–SP 314, pre-bend segment), maximum water depth is 3.408 m (outer bank), and the highest water surface elevation is 26.831 m above sea level (upstream boundary). The outer bank consistently exhibits higher velocities and water surface elevations than the inner bank, confirming superelevation and active scour at the concave bank. These findings provide critical hydrodynamic data for river bank protection and flood management planning along the Palu River corridor.